THE SPIRITUAL PATH OF CARYLL: Houselander - KEMP Joyce (New York , Mahwah Paulist Press, 2001)
In nine chapters, Joyce Kemp explores aspects of Caryll's life, from her difficult childhood, through periods of searching, being touched by God, becoming involved with the poor and the marginalized in society, living through war, writing and meeting an early death through cancer. Each chapter is followed by spiritual exercises inspired by the techniques of Drs. Ira Progoff and Jean Houston, that are built around the topic of that period of Caryll's life.